All-carbon lithium ion hybrid capacitor based on coal-based carbon material and preparation method thereof

By using coal-based porous carbon materials as the positive and negative electrode materials in lithium-ion capacitors and performing pre-lithiation treatment, the problems of high cost and difficult characteristics matching of existing lithium-ion capacitors are solved, and efficient and low-cost capacitor production is achieved.

CN120126946APending Publication Date: 2025-06-10XIAN THERMAL POWER RES INST CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510548185.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The high cost of the positive and negative electrode materials of existing lithium-ion capacitors and difficult to match capacity and power characteristics, limiting their large-scale manufacturing and commercialization.

Method used

A full carbon lithium-ion hybrid capacitor based on coal-based carbon material is used, and a coal-based porous carbon material is used in both the positive electrode and the negative electrode sheet, and the negative electrode is prelithiated to form an overall structure of a separator containing an electrolyte.

Benefits of technology

The good matching of positive and negative electrode capacity and power characteristics is achieved, which reduces the material cost and significantly reduces the production cost of lithium-ion capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120126946A_ABST
    Figure CN120126946A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of supercapacitors, and discloses an all-carbon lithium ion hybrid capacitor based on a coal-based carbon material and a preparation method thereof.The all-carbon lithium ion hybrid capacitor comprises a negative pole piece, a positive pole piece and a diaphragm containing electrolyte, the negative pole piece, the diaphragm containing the electrolyte and the positive pole piece are sequentially assembled into an integral structure; active materials of the positive pole piece and the negative pole piece are coal-based porous carbon materials; and the negative pole piece is a negative pole piece subjected to pre-lithiation. Active materials of the positive pole piece and the negative pole piece are coal-based porous carbon materials, so that the positive pole piece and the negative pole piece are easily matched with capacity and power characteristics of the positive pole and the negative pole, and the electrochemical performance of the carbon materials can be well exerted. Compared with positive and negative electrode materials of a current commercial lithium ion capacitor, the coal-based material is low in price, and the cost of the lithium ion capacitor can be remarkably reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of supercapacitors, and particularly relates to an all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials and a preparation method thereof. Background Art

[0002] Renewable energy, as an inexhaustible energy source, contributes to environmental protection and long-term sustainable development. However, renewable energy is intermittent. Therefore, the construction of an uninterrupted carbon-free energy system depends on energy storage systems. Two complementary electrochemical energy storage systems represented by lithium-ion batteries and supercapacitors play a crucial role in markets such as electric vehicles and portable electronic devices. Lithium-ion batteries can provide a relatively high energy density (150 - 200 Wh kg -1 ), but due to the slow kinetics of the diffusion process of lithium ions in the electrodes and the large volume change during charge and discharge, their power density (<1000 W kg -1 is relatively low and the cycle life (<1000 cycles) is very short. Supercapacitors, due to their highly reversible ion adsorption / desorption energy storage mechanism, exhibit a high power density (>5 kW kg -1 and long cycle stability (>100000 cycles), but they are greatly limited by a low energy density (<10 Wh kg -1 ). Lithium-ion hybrid capacitors are assembled from battery-type negative electrodes and capacitive positive electrodes in a lithium salt electrolyte, and have the advantages of high energy density, high power density, and long cycle stability, which is an important direction for the development of future energy storage devices.

[0003] Currently, the positive electrodes of lithium-ion capacitors are usually commercial activated carbon materials, and negative electrodes have developed materials such as alloys, metal / organic compounds, etc. Although these materials have excellent electrochemical properties, their costs are relatively high, which is not conducive to the large-scale manufacturing and commercialization of lithium-ion capacitors. In addition, when assembling lithium-ion capacitor devices, the matching of the capacity and power characteristics of the positive and negative electrodes is a key factor determining their performance. It is often difficult to match the capacity and power characteristics of different materials when assembling hybrid capacitors, and it can only be matched by controlling the mass ratio of the positive and negative electrodes, but it is difficult to fully utilize the characteristics of the materials.

[0004] The patent with application number 201710627442.2 and publication number CN 107248451 B invented a lithium-ion hybrid capacitor with a carbon material (activated carbon, activated carbon fiber or graphene) as the positive electrode and a silicon-carbon material as the negative electrode. It utilizes the high specific capacity of the silicon-based material (the theoretical specific capacity of silicon is 4200 mAh g -1),(slightly higher than the discharge platform of carbon materials), a lithium-ion capacitor with a high energy density is prepared. However, due to the mismatch between the capacity and power characteristics of carbon materials and silicon-carbon anodes, it is necessary to extensively try lithium-ion capacitors with different mass ratios of positive and negative electrodes to achieve a performance matching effect. In addition, silicon-carbon anodes are expensive, and the cost of manufacturing lithium-ion capacitors is relatively high, resulting in a large cost. Summary of the Invention

[0005] To solve the problems existing in the prior art, the purpose of the present invention is to provide an all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials and its preparation method. The present invention can solve the problems of high cost of commercial lithium-ion capacitors and difficulty in mass matching of positive and negative electrodes.

[0006] To achieve the above purpose, the present invention adopts the following technical solutions: An all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials, comprising a negative electrode sheet, a positive electrode sheet, and a separator containing an electrolyte. The negative electrode sheet, the separator containing an electrolyte, and the positive electrode sheet are assembled into an integral structure in sequence; the active materials of the positive electrode sheet and the negative electrode sheet both adopt coal-based porous carbon materials; the negative electrode sheet adopts a pre-lithiated negative electrode sheet.

[0007] Preferably, the preparation process of the positive electrode sheet includes: Mix the conductive agent, the binder, and the coal-based porous carbon material for the positive electrode, and after mixing, grind them into a film in absolute ethanol to obtain an electrode film. Then, vacuum-dry the obtained electrode film to obtain the positive electrode sheet.

[0008] Preferably, the mass ratio of the conductive agent, the binder, and the coal-based porous carbon material for the positive electrode is 1:1:(7-9), and the areal density of the positive electrode sheet is 0.9-1.1 g / cm 2 .

[0009] Preferably, the preparation process of the coal-based porous carbon material for the positive electrode includes: Pre-carbonize coal at 680-720 °C for 1-2 h to obtain carbon powder; Mix the carbon powder and potassium hydroxide in a mass ratio of 1:(3-5), and then heat it to 900-1000 °C in an inert atmosphere and keep it warm for activation for 1-2 h. After the heat preservation ends, cool it to obtain a porous carbon material; Wash the porous carbon material with hydrochloric acid and hydrofluoric acid repeatedly for 3-5 times, then wash it with deionized water until the solution is neutral, and then dry it to obtain the coal-based porous carbon material.

[0010] Preferably, the preparation process of the negative electrode sheet includes: The conductive agent, binder, and coal-based porous carbon material for the negative electrode are uniformly mixed with a solvent to form a slurry. The slurry is uniformly coated on a current collector, and then vacuum dried to obtain the negative electrode sheet.

[0011] Preferably, the preparation process of the coal-based porous carbon material for the negative electrode includes: Wash the coal powder with hydrochloric acid, hydrofluoric acid, and deionized water to remove impurities in the coal powder; Heat-treat the washed coal powder in a protective atmosphere at 900-1500 °C for 1-2 h to obtain the coal-based porous carbon material for the negative electrode.

[0012] Preferably, the mass ratio of the conductive agent, binder, and coal-based porous carbon material for the negative electrode is 1:1:(7-9); the solvent is 1-methyl-2-pyrrolidone; the current collector is copper foil, aluminum foil, carbon paper, or carbon cloth; after the slurry is uniformly coated on the current collector, the temperature of vacuum drying is 75-85 °C, and the drying time is 10-14 h.

[0013] Preferably, the conductive agent is one of conductive carbon black, acetylene black, and carbon nanotubes; the binder is one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.

[0014] Preferably, in the separator containing the electrolyte: The separator is a glass fiber separator, and the electrolyte is filled in the pores of the glass fiber separator; The electrolyte is an organic solution of lithium hexafluorophosphate. In the organic solution of lithium hexafluorophosphate, the concentration of lithium hexafluorophosphate is 0.9-1.1 mol L -1 , and the solvent is an organic solvent formed by mixing ethylene carbonate, diethyl carbonate, and dimethyl carbonate in an equal volume ratio.

[0015] The present invention also provides a preparation method of the all-carbon lithium-ion hybrid capacitor based on the coal-based carbon material as described above, including the following process: Pre-lithiate the negative electrode sheet; Then, in a protective atmosphere, assemble in the order of the negative electrode sheet, the separator containing the electrolyte solution, and the positive electrode sheet to obtain the all-carbon lithium-ion hybrid capacitor based on the coal-based carbon material.

[0016] The present invention has the following beneficial effects: In the all-carbon lithium-ion hybrid capacitor based on the coal-based carbon material of the present invention, the active materials of the positive electrode sheet and the negative electrode sheet are both coal-based porous carbon materials. Therefore, it is easy to match the capacities and power characteristics of the positive and negative electrodes, and the electrochemical performance of the carbon material can be well exerted. Compared with the positive and negative electrode materials of current commercial lithium-ion capacitors, the coal-based materials are inexpensive and can significantly reduce the cost of lithium-ion capacitors. Description of the Drawings

[0017] Figure 1 It is the rate performance graph of the coal-based porous carbon material for the positive electrode obtained in Example 1 of the present invention; Figure 2 It is the CV test curve graph of the coal-based porous carbon material for the positive electrode obtained in Example 1 of the present invention; Figure 3 It is the GCD curve graph of the coal-based porous carbon material for the positive electrode obtained in Example 1 of the present invention; Figure 4 It is the Ragone graph of the energy density and power density for the corresponding performance characterization of the hybrid capacitor prepared by assembling the positive electrode coal-based porous graphene and coal-based hard carbon in Example 1 of the present invention. Detailed implementation manners

[0018] To make the objectives, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are some, but not all, of the embodiments of the present invention. Usually, the components described and shown in the accompanying drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed present invention, but merely represents selected embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.

[0019] The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials of the present invention includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active materials in the positive electrode plate and the negative electrode plate both adopt coal-based carbon materials. The hybrid capacitor device is assembled in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate; the negative electrode needs to be pre-lithiated before assembly.

[0020] The coal-based carbon material for the positive electrode plate is high-specific-surface-area coal-based porous graphene prepared by pre-carbonization-potassium-based activation, and the active material in the negative electrode plate adopts coal-based hard carbon material.

[0021] The separator adopts a glass fiber separator. A pipette is used to drop the electrolyte onto the glass fiber separator so that the electrolyte fills the pores of the glass fiber separator. The electrolyte adopts an organic solution composed of lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate, and dimethyl carbonate. The concentration of lithium hexafluorophosphate in the organic solution is 0.9~1.1 mol L -1 , and ethylene carbonate, diethyl carbonate, and dimethyl carbonate are in equal volumes.

[0022] The preparation of the coal-based carbon material for the positive electrode tab includes the following steps: Step (1): Heat the coal material at a rate of 0.1~20 °C / min -1 to 680~720 °C, hold for 1~2 h for pre-carbonization. After the holding is completed, cool to obtain carbon powder.

[0023] Step (2): Directly mix the carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:(3~5), and heat to an activation temperature of 900~1000 °C in an inert atmosphere. After constant-temperature activation for 1~2 h, enter the cooling chamber to cool to room temperature to obtain a porous carbon material; Step (3): Wash the porous carbon material obtained in step (2) with HCl and HF repeatedly several times to remove impurities, then wash with deionized water until the solution is neutral, and dry to obtain the coal-based carbon material for the positive electrode tab.

[0024] The preparation of the coal-based hard carbon material for the negative electrode tab includes the following process: After the coal material is crushed and screened to obtain coal powder, wash the coal powder with HCl, HF and deionized water to remove impurities in the raw coal. Then use a programmed temperature horizontal tube furnace system to heat to 900~1500 °C in an argon atmosphere and heat-treat for 1~2 h to obtain the coal-based hard carbon material for the negative electrode tab.

[0025] The preparation process of the positive electrode tab is as follows: Uniformly mix the positive electrode active material (i.e., the coal-based carbon material for the positive electrode tab), the conductive agent and the binder in a mass ratio of (7~9):1:1 in absolute ethanol and grind into a film to obtain an electrode film. Dry the electrode film in a vacuum drying oven at 100~120 °C for 10~14 h for standby. Tear a 0.9~1.1 mg thin film from the dried electrode film to prepare a single-piece electrode with an area of 1 cm 2 (i.e., the positive electrode tab).

[0026] The preparation process of the negative electrode tab is as follows: Accurately weigh the negative electrode active material (i.e., the coal-based hard carbon material for the negative electrode tab), the conductive agent and the binder in a mass ratio of (7~9):1:1, and then use 1-methyl-2-pyrrolidone as a solvent to uniformly mix and make a slurry. Then evenly coat the slurry on the current collector, and then vacuum dry at 75~85 °C for 10~14 h.

[0027] After the negative electrode tab is manufactured, perform prelithiation on it. The prelithiation process is as follows: Make the lithium half-cell made of the negative electrode tab perform constant-current charge and discharge for three cycles at a current density of 0.03 A g -1 to complete the prelithiation of the negative electrode tab.

[0028] In the above solution, the conductive agent is one of conductive carbon black, acetylene black, and carbon nanotubes; the binder is one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose; the current collector is one of copper foil, aluminum foil, carbon paper, and carbon cloth.

[0029] When assembling the hybrid capacitor device in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate, in a glove box filled with high-purity argon, the above-mentioned prelithiated negative electrode plate, the separator containing the electrolyte, and the positive electrode plate are assembled in sequence into the all-carbon lithium-ion hybrid capacitor of the present invention based on coal-based carbon materials.

[0030] Example 1 The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials in this example includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active materials in the positive electrode plate and the negative electrode plate are both coal-based carbon materials. The hybrid capacitor is assembled into a hybrid capacitor device in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate; the negative electrode needs to be prelithiated before assembly.

[0031] The coal-based carbon material used for the positive electrode plate is high-specific-surface-area coal-based porous graphene prepared by pre-carbonization-potassium-based activation, and the active material in the negative electrode plate is coal-based hard carbon material.

[0032] The separator uses a glass fiber separator (in this example, the area of the glass fiber separator is 1 cm 2 ), and 180 μl of electrolyte is dropped into the glass fiber separator using a pipette. The electrolyte is an organic solution composed of lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate, and dimethyl carbonate, and the concentration of lithium hexafluorophosphate in the organic solution is 1.0 mol L -1 , and ethylene carbonate, diethyl carbonate, and dimethyl carbonate are of equal volume.

[0033] The preparation of the coal-based carbon material used for the positive electrode plate includes the following steps: Step (1), heating the coal material at a rate of 10 °C / min -1 to 700 °C, holding for 1 h for pre-carbonization. After the holding ends, it is cooled to obtain carbon powder.

[0034] Step (2), directly mixing the carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:4, and heating to an activation temperature of 900 °C in an inert atmosphere. After constant-temperature activation for 2 h, it enters the cooling chamber to be cooled to room temperature to obtain a porous carbon material; Step (3), washing the porous carbon material obtained in step (2) repeatedly with HCl and HF to remove impurities, and then washing with deionized water until the solution is neutral. After drying, the coal-based carbon material used for the positive electrode plate is obtained.

[0035] The preparation of the coal-based hard carbon material for the negative electrode plate includes the following process: The coal material is crushed and screened to obtain coal powder, and the coal powder is washed with HCl, HF and deionized water to remove impurities in the raw coal. Then, it is heated to 1300 °C and heat-treated for 1.5 h in an argon atmosphere using a programmed temperature horizontal tube furnace system to obtain the coal-based hard carbon material for the negative electrode plate.

[0036] The preparation process of the positive electrode plate is as follows: The positive electrode active material (i.e., the coal-based carbon material for the positive electrode plate), the conductive agent and the binder are uniformly mixed in anhydrous ethanol at a mass ratio of 8:1:1 and ground into a film to obtain an electrode film. The electrode film is dried in a vacuum drying oven at 110 °C for 12 h for standby. A 1.0 mg thin film is torn from the dried electrode film to prepare a single-piece electrode with an area of 1 cm 2 (i.e., the positive electrode plate).

[0037] The preparation process of the negative electrode plate is as follows: The negative electrode active material (i.e., the coal-based hard carbon material for the negative electrode plate), the conductive agent and the binder are accurately weighed according to a mass ratio of 8:1:1, and then uniformly mixed with 1-methyl-2-pyrrolidone as a solvent to form a slurry. Then, the slurry is uniformly coated on the current collector, and then vacuum dried at 80 °C for 12 h.

[0038] After the negative electrode plate is manufactured, it is pre-lithiated, and the pre-lithiation process is as follows: The lithium half-cell made of the negative electrode plate is subjected to constant current charge and discharge for three cycles at a current density of 0.03 A g -1 to complete the pre-lithiation of the negative electrode plate.

[0039] In the above solution, the conductive agent is conductive carbon black; the binder is 60% polytetrafluoroethylene emulsion; the current collector is copper foil.

[0040] When assembling the hybrid capacitor device in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate, in a glove box filled with high-purity argon, the pre-lithiated negative electrode plate, the separator containing the electrolyte, and the positive electrode plate are assembled in sequence into the all-carbon lithium-ion hybrid capacitor of this embodiment based on the coal-based carbon material.

[0041] The rate performance graph of the coal-based porous carbon material for the positive electrode obtained in this embodiment is as Figure 1 shown, and from Figure 1 it can be seen that the capacities of the coal-based porous carbon positive electrode half-cell at 0.1, 0.2, 0.5, 1, 2, 5, and 10 A / g are 122.7, 117.9, 112.9, 109.8, 108.1, 106.4, and 105.8 mAh / g, respectively.

[0042] The CV test curve of the coal-based porous carbon material for the positive electrode obtained in this example is as shown in Figure 2 As shown, from Figure 2 it can be seen that the CV curve of the coal-based porous carbon positive electrode presents a quasi-rectangle shape at a voltage of 2 - 4.5 V, proving that the energy storage mechanism of the coal-based porous carbon material is dominated by capacitive behavior.

[0043] The GCD curve of the coal-based porous carbon material for the positive electrode obtained in this example is as shown in Figure 3 As shown, from Figure 3 it can be seen that the GCD curve of the coal-based porous carbon material positive electrode presents a symmetric triangular shape, showing a standard electric double layer capacitor energy storage mechanism.

[0044] The Ragone plot of the energy density and power density of the corresponding performance characterization of the hybrid capacitor prepared from the assembled positive electrode coal-based porous graphene and coal-based hard carbon obtained in this example is as shown in Figure 4 As shown, from Figure 4 it can be seen that the maximum energy density of the hybrid capacitor is 171 Wh / kg, and the maximum power density is 8 kW / kg.

[0045] Example 2 The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials in this example includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active materials in the positive electrode plate and the negative electrode plate are both coal-based carbon materials. The hybrid capacitor device is assembled in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate; the negative electrode needs to be pre-lithiated before assembly.

[0046] The coal-based carbon material for the positive electrode plate is high specific surface area coal-based porous graphene prepared by pre-carbonization - potassium-based activation, and the active material in the negative electrode plate is coal-based hard carbon material.

[0047] The separator uses a glass fiber separator (in this example, the area of the glass fiber separator is 1 cm 2 ), and 180 μl of electrolyte is dropped into the glass fiber separator using a pipette. The electrolyte is an organic solution composed of lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate, and dimethyl carbonate. The concentration of lithium hexafluorophosphate in the organic solution is 1.1 mol L -1 , and ethylene carbonate, diethyl carbonate, and dimethyl carbonate are in equal volumes.

[0048] The preparation of the coal-based carbon material for the positive electrode plate includes the following steps: Step (1), heating the coal material at a rate of 1 °C / min -1 to 680 °C and holding for 2 h for pre-carbonization. After the holding is completed, carbon powder is obtained after cooling.

[0049] Step (2): Directly mix the carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:5, heat it to an activation temperature of 980 °C under an inert atmosphere, keep it at a constant temperature for activation for 1.5 h, and then enter the cooling chamber to cool to room temperature to obtain a porous carbon material; Step (3): Wash the porous carbon material obtained in step (2) repeatedly with HCl and HF to remove impurities, and then wash it with deionized water until the solution is neutral. After drying, a coal-based carbon material for the positive electrode plate is obtained.

[0050] The preparation of the coal-based hard carbon material for the negative electrode plate includes the following process: After the coal material is crushed and screened to obtain coal powder, wash the coal powder with HCl, HF and deionized water to remove impurities in the raw coal. Then use a programmed temperature horizontal tube furnace system to heat it to 900 °C in an argon atmosphere and heat-treat it for 2 h to obtain the coal-based hard carbon material for the negative electrode plate.

[0051] The preparation process of the positive electrode plate is as follows: Uniformly mix the positive electrode active material (i.e., the coal-based carbon material for the positive electrode plate), the conductive agent and the binder in a mass ratio of 7:1:1 in absolute ethanol and grind them into a film to obtain an electrode film. Dry the electrode film in a vacuum drying oven at 100 °C for 14 h for standby. Tear a 1.1 mg thin film from the dried electrode film to prepare a single-piece electrode with an area of 1 cm 2 (i.e., the positive electrode plate).

[0052] The preparation process of the negative electrode plate is as follows: Accurately weigh the negative electrode active material (i.e., the coal-based hard carbon material for the negative electrode plate), the conductive agent and the binder in a mass ratio of 9:1:1, and then uniformly mix them with 1-methyl-2-pyrrolidone as a solvent to make a slurry. Then uniformly coat the slurry on the current collector, and then vacuum dry it at 85 °C for 10 h.

[0053] The maximum energy density of the hybrid capacitor prepared from the assembled positive electrode coal-based porous graphene and coal-based hard carbon obtained in this example is 160 Wh / kg, and the maximum power density is 8 kW / kg.

[0054] Example 3 The all-carbon lithium-ion hybrid capacitor based on the coal-based carbon material in this example includes: a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. The active materials in the positive electrode plate and the negative electrode plate are both coal-based carbon materials. The hybrid capacitor device is assembled in the order of the negative electrode plate, the separator containing the electrolyte, and the positive electrode plate; the negative electrode needs to be pre-lithiated before assembly.

[0055] The coal-based carbon material for the positive electrode plate is high specific surface area coal-based porous graphene prepared by pre-carbonization-potassium-based activation, and the active material in the negative electrode plate is a coal-based hard carbon material.

[0056] The diaphragm used is a glass fiber diaphragm (in this embodiment, the area of the glass fiber diaphragm is 1 cm 2 ), and 180 μl of electrolyte is dropped onto the glass fiber diaphragm using a pipette. The electrolyte is an organic solution composed of lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate, and dimethyl carbonate. The concentration of lithium hexafluorophosphate in the organic solution is 0.9 mol L -1 , and ethylene carbonate, diethyl carbonate, and dimethyl carbonate are in equal volumes.

[0057] The preparation of the coal-based carbon material used for the positive electrode sheet includes the following steps: Step (1): Heat the coal material at a rate of 20 °C / min -1 to 720 °C and hold for 1.5 h for pre-carbonization. After the holding is completed, cool to obtain carbon powder.

[0058] Step (2): Directly mix the carbon powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:3, and heat to an activation temperature of 1000 °C in an inert atmosphere. After holding for 1 h at a constant temperature, enter the cooling chamber to cool to room temperature to obtain a porous carbon material; Step (3): Wash the porous carbon material obtained in step (2) repeatedly with HCl and HF to remove impurities, and then wash with deionized water until the solution is neutral. After drying, obtain the coal-based carbon material for the positive electrode sheet.

[0059] The preparation of the coal-based hard carbon material used for the negative electrode sheet includes the following process: After crushing and screening the coal material, coal powder is obtained. Wash the coal powder with HCl, HF, and deionized water to remove impurities in the raw coal. Then, use a temperature-programmed horizontal tube furnace system to heat to 1300 °C in an argon atmosphere and heat-treat for 1 h to obtain the coal-based hard carbon material for the negative electrode sheet.

[0060] The preparation process of the positive electrode sheet is as follows: Uniformly mix the positive electrode active material (i.e., the coal-based carbon material for the positive electrode sheet), the conductive agent, and the binder in a mass ratio of 9:1:1 in absolute ethanol and grind into a film to obtain an electrode film. Dry the electrode film in a vacuum drying oven at 120 °C for 10 h for standby. Tear off a 0.9 mg thin film from the dried electrode film to prepare a single-piece electrode with an area of 1 cm 2 (i.e., the positive electrode sheet).

[0061] The preparation process of the negative electrode plate is as follows: Weigh accurately the negative electrode active material (i.e., the coal-based hard carbon material used for the negative electrode plate), the conductive agent, and the binder according to a mass ratio of 7:1:1, and then use 1-methyl-2-pyrrolidone as the solvent to uniformly mix them into a slurry. Then, coat the slurry evenly on the current collector, and then vacuum dry it at 75 °C for 14 h.

[0062] In this embodiment, the maximum energy density of the hybrid capacitor assembled with the positive electrode coal-based porous graphene and coal-based hard carbon is 156 Wh / kg, and the maximum power density is 8 kW / kg.

[0063] Obviously, the described embodiments are only partial embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the scope of protection of the present invention.

[0064] Finally, it should be noted that: The above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the above embodiments, those of ordinary skill in the art should understand that: It is still possible to modify the specific implementation manners of the present invention or make equivalent replacements, and any modification or equivalent replacement without departing from the spirit and scope of the present invention shall be covered by the scope of the present invention.

Claims

1. A full-carbon lithium-ion hybrid capacitor based on coal-based carbon materials, characterized in that: It includes a negative electrode plate, a positive electrode plate and a separator containing an electrolyte, wherein the negative electrode plate, the separator containing an electrolyte and the positive electrode plate are sequentially assembled into an integral structure; the active materials of the positive electrode plate and the negative electrode plate are both made of coal-based porous carbon materials; the negative electrode plate is a pre-lithiated negative electrode plate.

2. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 1, characterized in that: The preparation process of the positive electrode sheet includes: The conductive agent, the binder and the coal-based porous carbon material for the positive electrode are mixed evenly, and then ground into a film in anhydrous ethanol to obtain an electrode film, and then the obtained electrode film is vacuum dried to obtain the positive electrode plate.

3. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 2, characterized in that: The mass ratio of the conductive agent, the binder and the coal-based porous carbon material for the positive electrode is 1:1:(7-9), and the surface density of the positive electrode sheet is 0.9-1.1 g / cm 2 .

4. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 2, characterized in that: The preparation process of the coal-based porous carbon material for the positive electrode comprises: Pre-carbonize the coal at 680-720°C for 1-2 h to obtain carbon powder; The carbon powder and potassium hydroxide are mixed in a mass ratio of 1: (3-5), and then heated to 900-1000° C. in an inert atmosphere for activation for 1-2 hours, and then cooled after the insulation to obtain a porous carbon material; The porous carbon material is repeatedly washed with hydrochloric acid and hydrofluoric acid for 3 to 5 times, then washed with deionized water until the solution is neutral, and then dried to obtain the coal-based porous carbon material.

5. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 1, characterized in that: The preparation process of the negative electrode plate includes: The conductive agent, the binder and the coal-based porous carbon material for the negative electrode are uniformly mixed with a solvent to prepare a slurry, the slurry is uniformly coated on the current collector, and then vacuum dried to obtain the negative electrode plate.

6. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 5, characterized in that: The preparation process of the coal-based porous carbon material for the negative electrode comprises: The coal powder is washed with hydrochloric acid, hydrofluoric acid and deionized water to remove impurities in the coal powder; The washed coal powder is heat treated at 900-1500 °C for 1-2 h in a protective atmosphere to obtain a coal-based porous carbon material for a negative electrode.

7. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 5, characterized in that: The mass ratio of the conductive agent, the binder and the coal-based porous carbon material for the negative electrode is 1:1:(7~9); the solvent is 1-methyl-2-pyrrolidone; the current collector is copper foil, aluminum foil, carbon paper or carbon cloth; after the slurry is evenly coated on the current collector, the vacuum drying temperature is 75~85°C and the drying time is 10~14h.

8. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 2 or 5, characterized in that: The conductive agent is one of conductive carbon black, acetylene black and carbon nanotubes; the binder is one of polyvinylidene fluoride, polytetrafluoroethylene and sodium carboxymethyl cellulose.

9. The all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to claim 1, characterized in that: In the separator containing the electrolyte: The diaphragm is a glass fiber diaphragm, and the electrolyte is filled in the pores of the glass fiber diaphragm; The electrolyte is an organic solution of lithium hexafluorophosphate, wherein the concentration of lithium hexafluorophosphate is 0.9-1.1 mol L -1 The solvent is an organic solvent prepared by mixing ethylene carbonate, diethyl carbonate and dimethyl carbonate in equal volume proportions.

10. The method for preparing the all-carbon lithium-ion hybrid capacitor based on coal-based carbon materials according to any one of claims 1 to 9, characterized in that: The process includes the following: Pre-lithiation of the negative electrode plate; Afterwards, in a protective atmosphere, the negative electrode sheet, the diaphragm containing the electrolyte, and the positive electrode sheet are assembled in order to obtain the all-carbon lithium-ion hybrid capacitor based on the coal-based carbon material.

Citation Information

Patent Citations

  • Lithium ion capacitor with high energy density

    CN107248451A

  • A high energy density lithium-ion capacitor

    CN107248451B